Feasibility of mean platelet volume as a biomarker for chronic obstructive pulmonary disease: A systematic review and meta-analysis. Issue 12 (December 2019) - Ma, Yiming; Zong, Dandan; Zhan, Zijie; Li, Herui; Dai, Zhongshang; Cui, Yanan; Luo, Lijuan; Zeng, Zihang; He, Chenjie; Chen, Yan
Objective: To evaluate the feasibility of mean platelet volume (MPV) as a biomarker for chronic obstructive pulmonary disease (COPD). Methods: A systematic search for studies published up to March 2019 was performed in the PubMed and Web of Science databases. Three independent investigators screened the titles and abstracts of including studies according to eligibility criteria. The Newcastle–Ottawa Scale was used to assess the quality of eligible studies, and statistical analyses were performed using Review Manager version 5.3. Results: A total of eight studies with 1230 COPD patients and 443 healthy controls were included in our meta-analysis. No significant differences in MPV level were identified in pairwise comparisons of the acute exacerbations of COPD (AECOPD), stable COPD, and control groups. Furthermore, no significant correlation was observed between MPV level and systemic inflammatory biomarkers. Conclusions: MPV does not appear to represent a suitable biomarker of disease phase or inflammatory burden in COPD. However, future large-scale studies should be performed to further investigate the relationship between MPV and COPD.